IMPORTANCE OF PINHÃO IN THE CONSERVATION OF ARAUCARIA FORESTS AND THE SOCIAL ROLE OF THE CONSUMER MARKET - Ávila, Bianca Pio; Henzel, Ana Beatriz Devantier; Foesch, Meri Diana Strauss; de Almeida, Eric Weller; Molina, Artur Ramos; Guarino, Ernestino de Souza Gomes (Floresta, 2023)
Araucaria forests are currently threatened with extinction, due to the disorderly exploitation and disorderly sale of their wood in the easly 20th. In regions where these forests are available, farmers sell araucaria seeds, the pinhão nut, as a way of adding income. Non-timber forest products (NTFP) are a source of livelihood for traditional forest communities and local farmers, as well as an alternative for territorial development. To ensure the effective maintenance of forest germplasm sustainably, the collective participation of these communities, farmers, government, and society is necessary. This study analyzes the consumption of pine nuts and how this consumption can affect the conservation of araucaria forests. Free word association technique and exploratory research were performed and a questionnaire containing 18 questions. The exploratory factorial analysis showed that four factors were sufficient to measure the main characteristics that should be considered to helps in the development of a production chain that benefits communities dependent on these resources, thereby encouraging the protection of forests. It was concluded that the conservation of the araucaria is linked to the perception of the consumers and that the valorization of the pinhão is only possible through the integration of farmers who are adept at sustainable agriculture, and society.